2011
DOI: 10.1088/0960-1317/21/2/025008
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics in silicon/polymer technology as a cost-efficient alternative to silicon/glass

Abstract: We investigate TMMF photopolymer as a cost-efficient alternative to glass for the leak-tight sealing of high-density silicon microchannels. TMMF enables low temperature sealing and access to structures underneath via lamination and standard UV-lithography instead of costly glass machining and anodic bonding. TMMF is highly transparent and has a low autofluorescence for wavelengths larger than 400 nm. As the photopolymer is too thin for implementing bulky world-to-chip interfaces, we propose adhesive bonding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…As a notable example for rapid prototyping using DFRs, Zhao et al introduced a process, ''do it yourself 3D microfluidic chips'', which is based on multilayer lamination of DFRs and patterning them by direct projection lithography using a commercially available digital projector [127]. More recently, different types of DFRs were used by several research groups for various biosensing applications [128][129][130]. Companies, such as DuPont (USA) [131], Engineered Materials Systems (USA) [132], Elga Europe (Italy) [133], Tokyo Ohka Kogyo Co. (Japan) [134], DJ DevCorp (USA) [135], are producing DFRs having thicknesses ranging from 5 lm to 1000 lm and in the form of sheets or rolls (up to 100 m long).…”
Section: New Prototyping Techniques Providing a Paradigm Shift For Sementioning
confidence: 99%
“…As a notable example for rapid prototyping using DFRs, Zhao et al introduced a process, ''do it yourself 3D microfluidic chips'', which is based on multilayer lamination of DFRs and patterning them by direct projection lithography using a commercially available digital projector [127]. More recently, different types of DFRs were used by several research groups for various biosensing applications [128][129][130]. Companies, such as DuPont (USA) [131], Engineered Materials Systems (USA) [132], Elga Europe (Italy) [133], Tokyo Ohka Kogyo Co. (Japan) [134], DJ DevCorp (USA) [135], are producing DFRs having thicknesses ranging from 5 lm to 1000 lm and in the form of sheets or rolls (up to 100 m long).…”
Section: New Prototyping Techniques Providing a Paradigm Shift For Sementioning
confidence: 99%
“…Prepare the substrate. Silicon with different types of doping is most commonly used substrate [15,16]. But other types of substrate can also easily be made on silicon wafers, like silicon dioxide, silicon nitride, depending on the applications.…”
Section: Microfluidicsmentioning
confidence: 99%
“…Becker and Locascio (2002) reviewed other materials including polymethyl methacrylate (PMMA) and polydimethylsiloxane (PDMS) which are commonly preferred in industries as cheaper alternatives to glass. Kalkandjiev et al (2011) highlighted the low fabrication cost and the ease to mass produce as the major reasons of using PDMS and PMMA, and Luo et al (2010) demonstrated that the PMMA also have the potential to create complex, stable geometries using simple fabrication methods (without fabricating energy directors), while being able to accommodate errors in terms of reversible change upon softening and melting.…”
Section: Introductionmentioning
confidence: 99%